Descripción del control de la Monturita Sibine apicalis en el cultivo de banano Musa paradisiaca. - Paredes Carrasco, Julio Alejandro (2024)
Ecuador is recognized internationally as one of the main producers and exporters of bananas, noted for the excellent quality and flavor of its product. Most of Ecuador's banana production is concentrated in the coastal region, specifically in three provinces (Los Ríos, Guayas and El Oro). Like any crop, it is exposed to the population incidence of pest insects, which directly affect its production and quality. The case of the monturita (Sibine apicalis) in banana crops (Musa paradisiaca) poses a significant challenge for producers due to the damage that this pest can cause in banana plantations. Its larval stage is the one that causes the most damage to the plant, since a single larva can consume more than 300 centimeters of leaves. Although chemical control through the application of insecticides is commonly mentioned to control Sibine spp., there are equally effective alternative methods. Among the main ones are biological control, cultural control and ethological control. These strategies are important to reduce dependence on insecticides and promote more sustainable integrated pest management.